What We Learned in 25 Years of Interactive Molecular Design Sessions. (10th August 2021) - Kuhn, Bernd; Haap, Wolfgang; Obst‐Sander, Ulrike; Kramer, Christian; Stahl, Martin
Abstract: We retrace Prof. François Diederich's consultancy work for Roche and its impact over the years he worked with us. François Diederich uniquely shaped our approach to molecular design, and interactions with him and his research group at ETH Zurich have created deep insights into molecular recognition. Herein we share how his style and approach continue to inspire us. Abstract : A lasting legacy : Prof. François Diederich has had a major impact on the evolution of molecular design work at F. Hoffmann – La Roche AG over a period of more than 25 years. This essay attempts to highlight what was unique about François' approach and how we can continue to learn from him.